PANDANGAN DUNIA DALAM NOVEL NORUWEI NO MORI KARYA MURAKAMI HARUKI: ANALISIS STRUKTURALISME GENETIK LUCIEN GOLDMANN - Dian Annisa Nur Ridha (Universitas Diponegoro, 2013)
ABSTRACT This research analyzes one of Murakami Haruki’s works entitled Noruwei no Mori. The novel tells about a man named Toru who keeps thinking about the death of his best friend, Kizuki. As Kizuki passes away, Toru gets closer with Kizuki’s girl, Naoko. Naoko gets a mental disorder due to Kizuki’s death. There comes Midori and other characters around the main characters, Toru and Naoko, who try to get them to forget the past and start thinking about the present. Naoko finally decides to kill herself while Toru lives with Midori without releasing his memory with Naoko and Kizuki. This research aims at observing the structure of the novel and the world’s view of the social class in the novel. Therefore, the research applies Lucien Goldmann’s theory on genetic structuralism. The result of the research shows that the title of the novel, that is Noruwei no Mori, is the same as one of the Beatles’ songs, that is Norwegian Wood. They also have the same structure. The elements of the structure are the past to remember, the present, the people who choose to live with one of them. The structure is also coherent with the Japanese social condition which has a tradition of Obon, that is annual ritual to commemorate the spirit of the ancestors. Noruwei no Mori has primary binary oppositions, those are intimacy and alienation. There are other binary oppositions that relates one to another. There are characters representing God, world, human. Man represented the character has to choose God, world, or both of them at once. The main character, Toru, chooses both God and world. He decides to live with Midori but never forgets his memory in the past with Kizuki and Naoko. That is the best life choice proposed by the story based on Japanese belief. A Japanese tries to keep the harmony (wa) as authentic values in life to balance himself with other people around him and the nature. However the harmony he keeps is not a real one but it is enough to keep him survive in the world. Keywords: World’s View, Harmony (wa), Noruwei no Mori, Murakami Haruki, Genetic Structuralism